Education About Posture Disorders In Elementary School Children - Bintang, Siti Sarah Bintang Sarah; Zein, Elvida Rahmi; Jannah, Miftahul; Handayani, Dwi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Postural disorders in children are abnormalities in body alignment that can lead to long-term musculoskeletal health issues. Poor posture can cause muscle imbalance, chronic pain, and even growth problems. Contributing factors include incorrect sitting habits, excessive gadget use, lack of physical activity, and heavy school bags. Education for children and parents on proper posture is an important strategy to prevent these issues. This community service activity was conducted in Sidodadi Village, Beringin District, involving elementary students and their parents. The results showed that the majority of participants were unaware of ideal posture and the importance of early detection of disorders such as kyphosis, scoliosis, and lordosis. Through this education, participants gained awareness about the importance of maintaining good daily habits to support healthy posture.